LA'FILTER Enterprise / Ungku Mazummar Ungku Mustaffa... [et al.] - Ungku Mustaffa, Ungku Mazummar; Bridgette, Borinus; Mohamed Noor, Deena Yusrina; Hadi Rosman, Muhammad Ashraf; Abd Razak, Muhammed Hakim (2020)
LA' FILTER sdn.bhd is an enterprise that includes design,manufacture and market department. Strictly conformed to the international standard and based on the introduction of the advanced technology, varieties of all series excellent elements enclosures and standard filters have been developed. We are a development and manufacturing organization producing straw filters and bottles to purify the drinking water.The founders of our company have a combined years of experience and are uniquely equipped to provide innovative solutions to industry problems.The company was founded in 2006.Over these years,the company has earned a reputation has a unique combination of quality,value,trust and reliability.Our company is located in Nilai, Negeri Sembilan.